(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents the design, simulation, and experimental validation of high-performance rectangular patch antennas and their arrays specifically designed for X-band radar applications. CST Microwave Studio was used to enhance the antenna designs, maximizing radiation efficiency and achieving optimal performance at 10 GHz with the appropriate impedance. Rogers RT5880 outperformed FR-4 across gain, reflection coefficient, and voltage standing wave ratio (VSWR) when compared with two substrates. The work culminated in the development of a four-element antenna array, achieving a remarkable gain of 11.82 dBi. The experimental measurements prove the validity of the simulated results, confirming that this design is viable and can be used in advanced satellite communications. Graphene is also explored as a conducting material due to its tunable electrical properties by chemical potential variations, and its performance is compared with that of conventional copper. All these novel improvements contribute to the development of next-generation reconfigurable antennas that offer greater flexibility and performance for high-quality satellite radar communication.